2020
DOI: 10.5194/se-11-1205-2020
|View full text |Cite
|
Sign up to set email alerts
|

Basin inversion and structural architecture as constraints on fluid flow and Pb–Zn mineralization in the Paleo–Mesoproterozoic sedimentary sequences of northern Australia

Abstract: Abstract. As host to several world-class sediment-hosted Pb–Zn deposits and unknown quantities of conventional and unconventional gas, the variably inverted 1730–1640 Ma Calvert and 1640–1575 Ma Isa superbasins of northern Australia have been the subject of numerous seismic reflection studies with a view to better understanding basin architecture and fluid migration pathways. These studies reveal a structural architecture common to inverted sedimentary basins the world over, including much younger exam… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 84 publications
0
8
0
Order By: Relevance
“…This polydeformed terrane has been affected by multiple extensional and compressional episodes due to its interaction with Laurentia to the east between ∼ 1800 and 1500 Ma (Betts et al, , 2008Gibson et al, 2018;Korsch et al, 2012;Olierook et al, 2022). The Leichhardt superbasin is the oldest exposed basin in the region, cropping out throughout the entire Mount Isa terrane (Gibson and Edwards, 2020;Neumann et al, 2006). A ∼ 20 Myr period of extensional activity was followed by a compressional event known as the Wonga Orogeny (Spence et al, 2022), possibly related to the accretion of the seismically imaged Numil province to the east (Blaikie et al, 2017).…”
Section: Selective Basin Inversion Due To Periodic Instabilities In T...mentioning
confidence: 99%
See 2 more Smart Citations
“…This polydeformed terrane has been affected by multiple extensional and compressional episodes due to its interaction with Laurentia to the east between ∼ 1800 and 1500 Ma (Betts et al, , 2008Gibson et al, 2018;Korsch et al, 2012;Olierook et al, 2022). The Leichhardt superbasin is the oldest exposed basin in the region, cropping out throughout the entire Mount Isa terrane (Gibson and Edwards, 2020;Neumann et al, 2006). A ∼ 20 Myr period of extensional activity was followed by a compressional event known as the Wonga Orogeny (Spence et al, 2022), possibly related to the accretion of the seismically imaged Numil province to the east (Blaikie et al, 2017).…”
Section: Selective Basin Inversion Due To Periodic Instabilities In T...mentioning
confidence: 99%
“…Early models of Pb-Zn ore formation at Mount Isa suggested that mineralisation occurred during basin formation and was facilitated by fluid transport along active normal faults (Betts et al, 2003;Betts and Lister, 2001). How-ever, more recent interpretations suggest that basin inversion strongly controlled the emplacement of Pb-Zn mineral systems as well as the development of petroleum systems in Mount Isa (Gibson and Edwards, 2020;Gibson et al, 2017). For the ca.…”
Section: Selective Basin Inversion: Implications For Metamorphism And...mentioning
confidence: 99%
See 1 more Smart Citation
“…Inverted basins are very common geological features and are found in multiple locations, for instance the North Sea area (Lamplugh, 1919;Glennie and Boegner, 1981;Nalpas et al, 1995;Evans et al, 2003;De Jager, 2003;Hansen et al, 2021), the Pyrenees and European Alps (Pfiffner, 1993;Ziegler et al, 1995;Kiss et al, 2020;Mencos et al, 2015;Lescoutre and Manatschal, 2020;Musso Piantelli et al, 2022), the Atlas Mountains (Vially et al, 1994), Iran (Boutoux et al, 2021), the Araripe Basin in northeastern Brazil (Marques et al, 2014), the Andes (Ferrer et al, 2022b, and references therein), offshore of Korea (Park et al, 2021), and China (Yu et al, 2021), as well as many other places around the globe (Letouzey, 1990;Lowell, 1995;Iaffa et al, 2011;Gibson and Edwards, 2020;Bosworth and Tari, 2021;Dooley and Hudec, 2020).…”
Section: Importance Of Basin Inversion Tectonicsmentioning
confidence: 99%
“…Fourth, basin inversion processes and related fluid flow may furthermore lead to the development of economical mineral resources and ore deposits (e.g. Pb-Z mineralizations and Fe-Cu-Au deposits, Sibson and Scott, 1998;Groves and Bierlein, 2007;Hageman et al, 2016;Gibson et al, 2017;Gibson and Edwards, 2020;Liang et al, 2021). Finally, a thorough understanding of basin evolution, including basin inversion, is also of great interest for geothermal energy projects since tectonic displacements can strongly affect the thermal profile of the subsurface (Sandiford, 1999;Edwards et al, 2015;Vidal and Genter, 2018;Doornenbal et al, 2019;Békési et al, 2020;Weibel et al, 2020;Willems et al, 2020).…”
Section: Importance Of Basin Inversion Tectonicsmentioning
confidence: 99%